1997
DOI: 10.1002/(sici)1097-4547(19971001)50:1<23::aid-jnr3>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of D2 receptor gene expression by transcription factor AP-1 in cultured cells

Abstract: The role of the transcription factor AP-1 in regulating D2 receptor transcriptional activity was investigated in D2 receptor expressing neuroblastoma cells, NB41A3, and in non-D2 receptor expressing CHO cells. Deletion of a region containing the putative AP-1 binding site resulted in a significant reduction in the activity in CHO cells; while the activity in NB41A3 cells was increased suggesting that the AP-1 site may differentially regulate D2 gene expression in these distinct cell types. However, both cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The intronic sequence 5¢ flanking the first coding exon revealed consensus initiator (Inr) and downstream promoter elements (DPE) as well as putative transcription factor binding sites for AP4, glucoccorticoid receptor (GR), NFkappaB, CREB, AP1, thyroid transcription factor 1 (TTF1), CAAT enhancer binding protein (CEBP), pituitary specific pou domain transcription factor (Pit1, GHF-1), aryl hydrocarbon/Arnt heterodimers (Ahr/Arnt), pituitary homeobox 1 (Ptx1), retinoic acid receptor-related receptor a (RARa), GATA, GC boxes and TATAlike sequences (DQ277010). It also contained elements identical to the enhancers reported in the rat D 2 R promoter (Wang et al 1997). Transient transfection assays of serial deletion constructs from this intronic sequence demonstrated promoter activity in COS-7, aT3 and TE671 cell lines except for the shortest construct, which did not include the putative transcription initiation site (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The intronic sequence 5¢ flanking the first coding exon revealed consensus initiator (Inr) and downstream promoter elements (DPE) as well as putative transcription factor binding sites for AP4, glucoccorticoid receptor (GR), NFkappaB, CREB, AP1, thyroid transcription factor 1 (TTF1), CAAT enhancer binding protein (CEBP), pituitary specific pou domain transcription factor (Pit1, GHF-1), aryl hydrocarbon/Arnt heterodimers (Ahr/Arnt), pituitary homeobox 1 (Ptx1), retinoic acid receptor-related receptor a (RARa), GATA, GC boxes and TATAlike sequences (DQ277010). It also contained elements identical to the enhancers reported in the rat D 2 R promoter (Wang et al 1997). Transient transfection assays of serial deletion constructs from this intronic sequence demonstrated promoter activity in COS-7, aT3 and TE671 cell lines except for the shortest construct, which did not include the putative transcription initiation site (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Further work will be necessary to understand the underlying mechanisms of AP‐induced DRD2 upregulation and oxidative stress. It has been reported that DRD2 expression is negatively controlled by DA receptor regulating factor (DRRF or KLF16) (Lee et al, 2003) and positively controlled by transcription factors specificity protein 1 (Sp1) and activator protein 1 (AP‐1) (Wang et al, 1997). It has been demonstrated that nuclear factor kappa B (NFκB) has a direct role in DRD2 upregulation by nerve growth factor on prolactinomas (Bontempi et al, 2007; Fiorentini et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding these interactions is important to drug development, and these observations may result from interactions at the level of transcriptional regulation. To date, work examining transcriptional regulation of D2R has focused on the sp family of transcription factors, AP-1, and zif 268 (Wang et al 1997;Yajima et al 1998;Takeuchi et al 2002). In addition, a link between these transcription factors and D1R agonists has been established (Nguyen et al 1992;Hope et al 1992Hope et al , 1994Couceyro et al 1994;Keefe and Gerfen 1995;Wang et al 1995;Wang and Mcginty 1995a, b;Turgeon et al 1997;Hope 1998;Zhang et al 2005;Milanovic et al 2006;Radwanska et al 2006).…”
Section: Significance Of Alterations In Gene Expression To Behavioralmentioning
confidence: 99%